Return-to-competition progression after exertional heat stroke in an adolescent runner: A case report - Rivera-Brown, A. M.; Correa, J. J.; Micheo, W. F. (Journal of Athletic Training, 2023)
A 14-year-old runner indigenous to the tropics collapsed during his first 10-km race in a hot and humid climate. Dizziness, stumbling, and loss of consciousness were symptoms of exertional heat stroke. Two days postcollapse, blood tests revealed elevated hepatic transaminases consistent with hepatic injury. We discuss the return-to-competition progression, which included a gradual increase in exercise duration, initially in a cool and then in a tropical climate, and 2 field-based (wet-bulb globe temperature > 29.0°C) running evaluations that simulated the environmental conditions and training intensity the athlete would encounter in his sport. The thermoregulatory results guided the training progression, his tolerance to running in the heat improved, blood values normalized, and he was cleared to compete in a tropical climate. This exploration case report presents a novel field-based protocol that replicates the physiological demands of training in the tropics to evaluate thermoregulatory responses during exercise-heat stress in young runners after exertional heat stroke to facilitate a safe return to competition.